Pengaruh Stres Kerja Terhadap Kinerja Karyawan pada Masa Pandemi Covid-19: Studi Literatur - Zulkarnain, Izzaura Windayani Putri; Moeheriono (Business Administration Dept. - Faculty of Social and Political Sciences, Hang Tuah University, 2022)
Coronavirus Disease has hit Indonesia in 2019, this pandemic has had a major impact on aspects of work in Indonesia. There are many fields that have been affected by this pandemic, one of which is in the field of employment. Many employees experience work stress during this pandemic, the main causes of work stress are workload, work time and work environment coupled with the Covid-19 pandemic conditions which limit the space to move so that it increases feelings of tirednessand boredom, pressure due to deadlines that will later affect employee performanceThis research is a literature study that discusses the Effect of Work Stress on Employees Performance During the Covid 19 Pandemic. The type of data used is secondary data, namely data obtained indirectly, this research data was obtained from 12 journals, 5 thesis and 1 proceedings, internet and other relevant sources that examine work stress during the Covid-19 pandemic and this study uses 15 theories that explain work stress and employee performance. This study aims to analyze the effect of work stress on employee performance and analyze stressors that affect employee performance during the pandemic. The results of the study show that job stress has an influence on employee performance. Work stress can have a positive and negative effect on employee performance. Work stress has a positive effect if an employee considers a stress to be a challenge and motivation so that employees can develop and be more responsible for their work, this can increase the level of employee performance, but if the stress experienced by employees has a negative effect it can reduce employee performance, because employees consider that stress is a demand, obstacle and pressure so that it can cause employees to feel depressed, easily tired and even make employees lazy to work.